Uncombable hair syndrome with loose anagen syndrome: A rare association - Divya Agrawal; Syed Suhail Amin; Mohammad Adil; Annu Priya (Wolters Kluwer Medknow Publications, 2020)
Uncombable hair syndrome presents with dry, coarse, silvery hairs that stand straight from the scalp surface. Loose anagen syndrome is characterized by easy pluckability of the hair due to impaired adhesion between the cuticle of the inner root sheath and the cuticle of the hair shaft. We report the case of a 7-year-old female who presented with features of both these conditions. She had difficulty in combing hair for 4 years. Her hairs did not grow and were dry and frizzy. Hairs were easily pluckable, and microscopy showed predominantly dystrophic anagen hair, with the shaft having undulations and longitudinal groove.